OP0006 Safety and efficacy of lenabasum (JBT-101) in diffuse cutaneous systemic sclerosis subjects treated for one year in an open-label extension of trial jbt101-ssc-001. (12th June 2018) - Spiera, R.; Hummers, L.; Chung, L.; Frech, T.; Domsic, R.; Hsu, V.; Furst, D.E.; Gordon, J.; Mayes, M.; Simms, R.; Lee, E.; Dgetluck, N.; et al.
Abstract : Background: Lenabasum (JBT-101) is a selective cannabinoid receptor type 2 agonist that activates resolution of innate immune responses in humans and reduces inflammation and fibrosis in animal models of SSc. It is a synthetic, oral, non-immunosuppressive small molecule. Lenabasum had acceptable safety and tolerability and showed evidence of clinical benefit in diffuse cutaneous SSc (dcSSc) in Phase 2 trial JBT101-SSc-001 (NCT02465437 ). Objectives: The objective of this study was to provide long-term open-label safety and efficacy data in dcSSc subjects who received lenabasum in that trial. Methods: Subjects who completed the double-blind placebo-controlled (DBPC) part of JBT101-SSc-001 were eligible to receive lenabasum 20 mg BID in an open-label extension (OLE). Results: 36/38 (95%) eligible subjects enrolled in the OLE and 34/36 (94%) were on baseline immunosuppressive drugs. The mean interval off study drug from the end of DBCP dosing to the start of OLE dosing of 9.5 weeks (range 4.7 to 56 weeks). At the time of data cut-off, the duration of OLE dosing was median 51.4 weeks, mean 45 weeks (range 26, 418 weeks), and 19 subjects had completed Week 60. Three subjects discontinued, 2 for AEs and 1 for withdrawal of consent. Adverse events (AEs, n=171) occurred in 33/36 (92%) subjects in the OLE. By maximum severity, 1 (3%) subject had life threatening AE, 3 (8%) subjects had severe AEs, 21 (58%) subjects had moderate AEs and 8 (22%) had mild AEs. Seven (19%) subjects had AEs considered related to lenabasum. The AEs that occurred in ≥10% of subjects (n, % of subjects) were upper respiratory tract infection (8, 22%), urinary tract infection (5, 14%), diarrhoea (4, 11%) and skin ulcers (4, 11%). Mild intermittent dizziness occurred in 3 (8%) subjects. One subject developed renal crisis 7 days after starting 60 mg/day prednisone prescribed by a non-study physician and had 2 severe and 1 life-threatening/serious AEs related to the renal crisis and deemed unrelated to lenabasum. During the OLE, there was improvement in multiple efficacy outcomes from both the study start and the OLE start. For example, in the 25 subjects who had completed OLE Week 52 at the time of data cut-off, the mean (SE) improvements from study start were: ACR CRISS score=56% (9%); modified Rodnan Skin Score=-8.6 (1.5); HAQ-DI=-0.14 (0.11), Physician Global Assessment=-0.9 (0.5), and 5-D Itch Questionnaire=-2.3 (0.8). Forced vital capacity% predicted was stable from study start with mean (SE) change=0.4% (0.7%). Conclusions: In OLE of Phase 2 trial JBT101-SSc-001, lenabasum continues to have acceptable safety and tolerability in dcSSc with no severe or serious AEs. Multiple efficacy outcomes improved, although open-label nature of dosing with lenabasum is acknowledged. These data support Phase 3 testing of lenabasum for treatment of dcSSc. Disclosure of Interest: R. Spiera: None declared, L. Hummers: None declared, L. Chung: None declared, T. Frech: None declared, R. Domsic: None declared, V. Hsu: None declared, D. Furst: None declared, J. Gordon: None declared, M. Mayes Consultant for: Boehringer-Ingelheim, Mitsubishi-Tanabe, Astellas, Roche-Genentech, R. Simms: None declared, E. Lee Employee of: Corbus Pharmaceuticals, Inc., N. Dgetluck Employee of: Corbus Pharmaceuticals, Inc., S. Constantine Employee of: Corbus Pharmaceuticals, Inc., B. White Employee of: Corbus Pharmaceuticals, Inc.